Perancangan Desain Karakter “Buyung dan Upik” Sebagai Upaya Mengajarkan Kesetaraan Gender Untuk Anak Usia Dini - Kemalasari, Rita (Journal of Animation and Games Studies, 2024)
This research aims to design attractive and educational character designs to teach the concept of gender equality to early childhood children. Character design is a pre-production stage in making of films or animated videos, games, comics, illustrated books, and other media as a means of education and information dissemination. Through the designed characters, children are invited to understand that every individual has the same rights and opportunities in every aspect of life, regardless of their gender. This can be taught from the family environment. One example is sharing roles in household chores. This research method uses a creative thinking process based on Wallas' theory, consisting of four stages: preparation, incubation, illumination, and verification. The designed characters are figures of sisters and brothers “Buyung and upik”who have different natures and characters but always share roles and work at home. The results of this study are expected to produce character designs that are not only attractive to early childhood children but also effective in conveying messages about gender equality.